The Syrian Orthodox Christians in the Late Ottoman period and beyond - Dinno, Khalid S. (Piscataway, NJ)
xx, 506 sayfa
Keywords: “The book addresses the history of Syrian Orthodoxy during a critical juncture of its history that spans the late Ottoman period and treads well beyond to witness remarkable revival, indeed renaissance. The work uniquely utilizes over 6000 uncatalogued and unpublished archival documents that were made available for it“--